ERAS (Enhanced Recovery After Surgery) pada Pasien Medically Compromised - Sasti Insana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Enhanced Recovery After Surgery (ERAS) protocol has gained significant attention in recent years, particularly in its application to patients with compromised medical conditions. This protocol aims to optimize perioperative care, reduce the stress associated with surgery, and improve recovery outcomes. Literature reviews indicate that ERAS is beneficial across various surgical disciplines, including colorectal, neurosurgery, and orthopedics, particularly in elderly populations and patients with comorbidities. Studies show that ERAS reduces postoperative complications, hospital stays, and enhances patient satisfaction. Furthermore, it emphasizes a holistic approach to recovery, addressing not only physical but also mental and emotional well-being. Implementations of ERAS protocols in high-risk surgical scenarios, such as gastrointestinal and head and neck surgeries, underscores its relevance for medically compromised patients. The evidence supports the effectiveness of ERAS in improving clinical outcomes and promoting faster recovery, which is crucial for patients with complex health conditions.